Identification of copper (Cu) stress-responsive grapevine microRNAs and their target genes by high-throughput sequencing. Issue 1 (23rd January 2019) - Jiu, Songtao; Leng, Xiangpeng; Haider, Muhammad Salman; Dong, Tianyu; Guan, Le; Xie, Zhenqiang; Li, Xiaopeng; Shangguan, Lingfei; Fang, Jinggui
Abstract : MicroRNAs (miRNAs) are a class of single-stranded non-coding small RNAs (sRNAs) that are 20–24 nucleotides (nt) in length. Extensive studies have indicated that miRNAs play important roles in plant growth, development and stress responses. With more copper (Cu) and copper containing compounds used as bactericides and fungicides in plants, Cu stress has become one of the serious environmental problems that affect plant growth and development. In order to uncover the hidden response mechanisms of Cu stress, two small RNA libraries were constructed from Cu-treated and water-treated (Control) leaves of 'Summer Black' grapevine. Following high-throughput sequencing and filtering, a total of 158 known and 98 putative novel miRNAs were identified in the two libraries. Among these, 100 known and 47 novel miRNAs were identified as differentially expressed under Cu stress. Subsequently, the expression patterns of nine Cu-responsive miRNAs were validated by quantitative real-time PCR (qRT-PCR). There existed some consistency in expression levels of Cu-responsive miRNAs between high throughput sequencing and qRT-PCR assays. The targets prediction of miRNAs indicates that miRNA may regulate some transcription factors, including AP2, SBP, NAC, MYB and ARF during Cu stress. The target genes for two known and two novel miRNAs showed specific cleavage sites at the 10th and/or 11th nucleotide from the 5′-end of the miRNA corresponding to their miRNA complementary sequences. The findings will lay the foundation for exploring the role of the regulation of miRNAs in response to Cu stress and provide valuable gene information for breeding some Cu-tolerant grapevine cultivars.